2020
DOI: 10.1093/jrr/rraa016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-ray dose rates higher than 8 Gy/min on the functioning of cardiac implantable electronic devices

Abstract: Direct irradiation may cause malfunctioning of cardiac implantable electronic devices (CIEDs). Therefore, a treatment plan that does not involve direct irradiation of CIEDs should be formulated. However, CIEDs may be directly exposed to radiation because of the sudden intrafractional movement of the patient. The probability of CIED malfunction reportedly depends on the dose rate; however, reports are only limited to dose rates ≤8 Gy/min. The purpose of this study was to investigate the effect of X-ray dose rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The application of PLA in medical instruments potentially opens up its possibility for internal dosimetry, yet the dose levels for radiotherapy thus far are generally no more than 100 Gy [ 16 , 17 ]. However, potentials still lie in the dosimetry in X-ray facilities, where the dose rate could reach 480 Gy/h [ 18 ], and in food packaging and sterilization industries, where the dose applied could reach 10 kGy [ 5 ] and above for chem-bio agent defeat. Significantly higher levels of gamma dose must be considered when deciding on the choice of polymer materials for radiation-sterilized products [ 19 ]–for the most part through 100 kGy and even toward 4000 kGy depending on the specific polymer chosen.…”
Section: Problem Formulation-research Framework/objectives On Advanci...mentioning
confidence: 99%
“…The application of PLA in medical instruments potentially opens up its possibility for internal dosimetry, yet the dose levels for radiotherapy thus far are generally no more than 100 Gy [ 16 , 17 ]. However, potentials still lie in the dosimetry in X-ray facilities, where the dose rate could reach 480 Gy/h [ 18 ], and in food packaging and sterilization industries, where the dose applied could reach 10 kGy [ 5 ] and above for chem-bio agent defeat. Significantly higher levels of gamma dose must be considered when deciding on the choice of polymer materials for radiation-sterilized products [ 19 ]–for the most part through 100 kGy and even toward 4000 kGy depending on the specific polymer chosen.…”
Section: Problem Formulation-research Framework/objectives On Advanci...mentioning
confidence: 99%
“…A recent study investigated the effects of x-ray dose rates of 4 to 24 Gy/min on CIED function and found that a dose rate >8 Gy/min would cause a temporary malfunction due to interference. 42 It had been recommended that in low-risk patients with the presence of an ICD and medium-risk patients with CIED, a weekly device check during the RT is recommended. 8 In high-risk patients, device evaluation within 24 hours after each fraction is needed.…”
Section: Management Of Commonly Seen Implanted Devices In Rt Patientsmentioning
confidence: 99%
“…FFF beams may induce malfunction depending on the dose rate in vitro [ 14 ]. High dose-rate X-rays may induce overcurrent on the circuit, which creates a high potential risk to CIEDs even if the radiation does not generate secondary neutrons.…”
Section: Management Of Cied Patient and Radiotherapymentioning
confidence: 99%